2013
DOI: 10.1080/02619768.2013.870994
|View full text |Cite
|
Sign up to set email alerts
|

ePortfolios beyond pre-service teacher education: a new dawn?

Abstract: The context of this paper is the final phase of a longitudinal action research project investigating whether an ePortfolio, created as a pre-service teacher to evidence a digital story of developing professional identity, could transition into employability, ie the first year as a newly qualified teacher. Thus this paper focuses on a new area of ePortfolio related research in teacher education; the transition from university into employment. The research findings indicate a changing purpose of the ePortfolio f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Along these lines, the portfolio provides a focus for development of e-learning skills, as it facilitates use of new technologies in compiling the portfolio (Spendlove & Hopper, 2006). In addition to these studies, extensive research has analysed the use of the electronic portfolio in training future teachers (Boulton, 2014;Ntuli, Keengwe & Kyei-Blankson, 2009;Ritzhaupt, Parker & Ndoye, 2012;Tochon, 2012;Trent & Shroff, 2013), and studies centre on the electronic portfolio as a learning tool in teacher education.…”
Section: Electronic Portfolios In Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, the portfolio provides a focus for development of e-learning skills, as it facilitates use of new technologies in compiling the portfolio (Spendlove & Hopper, 2006). In addition to these studies, extensive research has analysed the use of the electronic portfolio in training future teachers (Boulton, 2014;Ntuli, Keengwe & Kyei-Blankson, 2009;Ritzhaupt, Parker & Ndoye, 2012;Tochon, 2012;Trent & Shroff, 2013), and studies centre on the electronic portfolio as a learning tool in teacher education.…”
Section: Electronic Portfolios In Teacher Educationmentioning
confidence: 99%
“…In fact, this tool might help students to articulate their learning through the process of reflection and communication it promotes. Whereas some studies of reflection are oriented to professionals in the fields of school counsellor and school psychology education (Wakimoto & Lewis, 2014), most address pre-service education professionals (Boulton, 2014;Lopez-Fernandez & Rodriguez-Illera, 2009;Tochon, 2012).…”
Section: Electronic Portfolios As a Teaching And Learning Toolmentioning
confidence: 99%
“…Nevertheless, previous research indicates that on-going and process-oriented feedback is beneficial to build pre-service teachers' abilities to use technology in the classroom (Authors, 2012;Boulton, 2014).…”
Section: The Sqd-scalementioning
confidence: 99%
“…Samardzija and Balaban (2014) also suggest that they can be used to help academics design their career aspirations, and for institutions to support this development. For students, ePortfolios have the benefit of allowing them unlimited storage space (Ledoux & McHenry, 2006;Ntuli, Keengwe, & KyeiBlankson, 2009), assisting them in becoming reflective practitioners (Chambers & Wickersham, 2007;Ledoux & McHenry, 2006), and as a possible tool for future employment (Boulton, 2014;Goldsmith, 2007;Heinrich et al, 2007). Ledoux and McHenry (2006), however, have identified some barriers and challenges to implementing ePortfolios in a tertiary setting.…”
Section: Tertiary (Higher Education) Sectormentioning
confidence: 99%
“…These advantages include the ability to link entries, ease of access and opportunities for contributions which could include "collaboration and feedback" (p. 656). Heinrich et al (2007) concluded that ePortfolios are a valuable tool for on-going reflection (a key component of life-long learning), that they are valuable to industry regarding whom to employ (Boulton, 2014;Goldsmith, 2007), and as a tool for on-going professional development and as evidence for professional bodies (such as the Education Council of New Zealand).…”
Section: Tertiary (Higher Education) Sectormentioning
confidence: 99%